2011
DOI: 10.1128/jvi.05423-11
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Depletion of Hepatoma Cells Impairs Hepatitis B Virus Envelopment by Altering the Topology of the Large Envelope Protein

Abstract: Previous reports have shown that cholesterol depletion of the membrane envelope of the hepatitis B virus (HBV) impairs viral infection of target cells.A potential function of this lipid in later steps of the viral life cycle remained controversial, with secretion of virions and subviral particles (SVP) being either inhibited or not affected, depending on the experimental approach employed to decrease the intracellular cholesterol level. This work addressed the role of host cell cholesterol on HBV replication, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 53 publications
(49 reference statements)
1
30
0
Order By: Relevance
“…In persons infected with HCV, statins have also been demonstrated to inhibit viral replication via depletion of mevalonate which leads to low levels of geranylgeranyl phosphate which is needed for HCV replication (30). In persons infected with HBV, a possible mechanism of action is simply the lowering of cholesterol levels as cholesterol depletion impairs the ability of HBV to infect target cells (31). …”
Section: Discussionmentioning
confidence: 99%
“…In persons infected with HCV, statins have also been demonstrated to inhibit viral replication via depletion of mevalonate which leads to low levels of geranylgeranyl phosphate which is needed for HCV replication (30). In persons infected with HBV, a possible mechanism of action is simply the lowering of cholesterol levels as cholesterol depletion impairs the ability of HBV to infect target cells (31). …”
Section: Discussionmentioning
confidence: 99%
“…2 and 38) and small proteins of less than 50 amino acids (36). The L envelope protein of hepatitis B virus (48) exists in two functionally distinct topological isoforms whose topological distribution varies with the endoplasmic reticulum cholesterol content (49), which reciprocally affects a translocation of positively charged domains and marginally hydrophobic segments (50). It was suggested that cholesterol can either trigger conformational changes in the translocon by affecting the fluidity of the lipid bilayer or may change the surface charge distribution of the membrane and modulate electrostatic lipid-protein interactions (50).…”
Section: Discussionmentioning
confidence: 99%
“…This work thus provides direct in vivo experimental evidence showing that HBV infection is intimately linked to bile acid and lipid metabolism. Moreover, cholesterol has been implicated in HBV morphogenesis and infectivity, and promotion of cholesterol synthesis and uptake may be important in HBV infection (Bremer et al 2009, Dorobantu et al 2011.…”
Section: Perspectives On the Role Of The Receptor In Hbv Pathogenesismentioning
confidence: 99%